Copper‐Catalyzed Synthesis of a Highly Hydroxy‐Functionalized Benzo[e]indolizidine by Intramolecular N‐Arylation1. Issue 22 (17th June 2013) - Cordero, Franca M.; Khairnar, Bhushan B.; Bonanno, Paola; Martinelli, Andrea; Brandi, Alberto
Abstract: The enantiopure (2 S, 3 S, 3a S, 5 S )‐1, 2, 3, 3a, 4, 5‐hexahydropyrrolo[1, 2‐ a ]quinoline‐2, 3, 5‐triol (2, 3, 5‐trihydroxybenzo[ e ]indolizidine) framework has been synthesized by a straightforward strategy consisting of 1, 3‐dipolar cycloaddition of a pyrroline N ‐oxide to 2‐bromostyrene followed by isoxazolidine N–O bond reduction and cyclization by copper‐catalyzed nucleophilic aromatic substitution of the intermediate pyrrolidine. Abstract : Highly hydroxy‐functionalized hexahydropyrrolo[1, 2‐ a ]quinolines that have the same absolute configuration at stereocenters C‐2, C‐3 and C‐3a as natural lentiginosine have been synthesized through a three‐step sequence starting from enantiopure dialkoxypyrroline N ‐oxides derived fromL ‐tartaric acid.